An Analysis of Writing Achievement Among Personality Type At The Third Semester Students of English Department IAIN Bengkulu - Yashori Revola (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2016)
The objective of this research was to investigate the significance difference among personality type in their writing achievement. The population of the research consisted of the third semester students of English department of IAIN Bengkulu academic year 2015/2016. The research design was ex post facto design. The data in this study was analyzed with one-tailed t-test formula in SPSS 20 to calculate the differences of writing achievement among personality types with the level significance of α = 0.05. The result showed that there was difference among the mean score of introvert group, which was (82.32), the mean score of extrovert group (74.14), and the mean score of ambivert group (74.59). Firstly, the results between introvert and extrovert types were computed with statistic analysis and it showed that t count = 5,80 and t table = 2,02. Therefore, as t count > t table the alternative hypothesis was accepted. It means that the students of introvert type had better result than extrovert type in writing skill. Secondly, the result of statistic analysis between introvert and ambivert types showed that the value t count = 3,95 and t table = 2,02. It means that the students of introvert type had better result than ambivert type in writing skill. Thus, the alternative hypothesis was accepted. Thirdly, the result on statistic analysis between extrovert and ambivert types showed that the value t count = 0,21, t table = 2,02. It means that the students of extrovert type had almost the same result with ambivert type in writing skill. The conclusion is there was significance difference writing achievement between introvert and both of extrovert and ambivert types. Meanwhile, there was not significance difference writing achievement between extrovert and ambivert types